372. Analysis of the reliability of rapid diagnostic tests for varicella patients, including breakthrough cases. (15th December 2022) - Higashimoto, Yuki; Hattori, Fumihiko; Kawamura, Yoshiki; Kozawa, Kei; Enya, Yasuko; Ihira, Masaru; Yoshikawa, Tetsushi
Abstract: Background: In the era of universal varicella vaccination, diagnosis of varicella is challenging, especially for breakthrough cases. We sought to clarify the reliability of direct varicella-zoster virus (VZV) loop-mediated isothermal amplification (LAMP) and DermaQuick® VZV using the immunochromatography technique as rapid diagnostic tests for varicella. In addition, the usefulness of saliva as a sample type for direct LAMP was also investigated. Methods: Between April 2019 and January 2021, 46 patients suspected VZV infection were enrolled in this study. Written informed consent was obtained from the parents of all participants. This study was approved by the institutional review board of Fujita Health University (No. 15–247). Samples were collected from skin eruptions using two different swabs. one swab which was soaked in 1 mL of isotonic saline was used for direct VZV LAMP and the other swab which was immersed in 500 µL of DermaQuick® VZV reaction buffer was used for DermaQuick® VZV. The isotonic saline solution used to wash the oral swab sample was used for direct VZV LAMP. The DNA extracted from the solutions were used for real-time PCR analysis. Results: Thirty one patients (67.3%) were diagnosed with varicella based on real-time PCR of skin swabs. Direct LAMP of skin swabs was positive in 29 (63.0%) of 46 patients. DermaQuick® VZV was positive in 25 (54.3%) of 46 patients. The sensitivity for direct LAMP of skin swabs, DermaQuick® VZV, direct LAMP of oral swabs, and real-time PCR of oral swabs was 93.6% (95% confidence interval [CI], 79.3–98.9%), 80.7% (95% CI, 63.7–90.8%), 48.3% (95% CI, 32.0–65.1%), and 74.2% (95% CI, 56.8–86.3%), respectively. The sensitivity and specificity of real-time PCR for DNA extracted from oral swabs was 74.2% (95% CI, 56.8–86.3%) and 93.3% (95% CI, 79.8–99.7%), respectively. Conclusion: Although DermaQuick® VZV is the most convenient point-of-care test for varicella, the sensitivity and specificity of this method were slightly lower than those of direct VZV LAMP. Disclosures: All Authors : No reported disclosures.